(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rachmawati A, Yustian I, Pujiastuti Y, Suparman Shk, Arinafril. 2023. Biotic and dragonfly diversity indices as ecological quality evaluation in Lahat District Rivers, South Sumatra, Indonesia. Biodiversitas 24: 6059-6068. The Lematang, Sandaran, and Kungkilan rivers have been reported to be polluted by coal mining activities. This study aimed to evaluate the ecological conditions using a dragonfly as a bio-indicator. Dragonfly surveys were conducted using direct observation procedures in 11 research sites determined by purposive sampling based on positions of the upstream, midstream and downstream of the river entering the coal mining area, including settling ponds managing waste from post-mining activities (stockpiles and disposal). Dragonflies were captured by visual observations, direct capture, and sticky traps. Data were analyzed by calculating the Dragonfly Biotic Index (DBI) and Diversity Index. The correlation between dragonflies and environmental factors was analyzed using Canonical Correspondence Analysis (CCA) according to Jaccard’s index. The results showed there were 23 species of dragonflies. Larvae and exuviae were found in Aeshnidae and Libellulidae families. Dragonfly species with the highest DBI values were seen in Rhyothemis triangularis, Tholymis tillarga, Zyxomma petiolatum, Atrocalopteryx atrata, Libellago lineata and Rhinocypha fenestrata. Sandaran River had the highest DBI value and diversity index because of the undisturbed condition of the area, which had natural vegetation and unpolluted water conditions. The Kungkilan River will become the focus of river rehabilitation, starting with the reclamation of the river riparian area.